2022
DOI: 10.1007/s40273-022-01177-z
|View full text |Cite
|
Sign up to set email alerts
|

Are We Agreed? Self- Versus Proxy-Reporting of Paediatric Health-Related Quality of Life (HRQoL) Using Generic Preference-Based Measures: A Systematic Review and Meta-Analysis

Abstract: Objective The aim of this study was to examine the level of agreement between self-and proxy-reporting of health-related quality of life (HRQoL) in children (under 18 years of age) using generic preference-based measures. Methods A systematic review of primary studies that reported agreement statistics for self and proxy assessments of overall and/or dimension-level paediatric HRQoL using generic preference-based measures was conducted. Where available, data on intraclass correlation coefficients (ICCs) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…The lowest correlation of 0.64 was reached for the subdomain (I) general quality of life and attitude to the disease since this subdomain includes the most personal items like emotional wellbeing or concerns about the future. A meta-analysis of self- and proxy-reports of HRQoL in children also showed that the inter-rater agreement was lower for psychosocial-related domains such as emotion and cognition than for more observable domains relating to physical health and functioning [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lowest correlation of 0.64 was reached for the subdomain (I) general quality of life and attitude to the disease since this subdomain includes the most personal items like emotional wellbeing or concerns about the future. A meta-analysis of self- and proxy-reports of HRQoL in children also showed that the inter-rater agreement was lower for psychosocial-related domains such as emotion and cognition than for more observable domains relating to physical health and functioning [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both ECOG and HRQoL are independent health evaluations performed by clinicians and patients themselves. It has been suggested that the health status rated by the pediatric patients alone is not comprehensive ( 24 ) where bigger differences existed between proxy-reported and self-reported health outcomes in measuring pediatric patients than adults ( 25 ). Therefore, the agreement between the two health indicators can serve as a validation of our results.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest correlation of 0.64 was reached for the subdomain (I) general quality of life and attitude to the disease since this subdomain includes the most personal items like emotional wellbeing or concerns about the future. A meta-analysis of self-and proxy-reports of HRQoL in children also showed that the inter-rater agreement was lower for psychosocial-related domains such as emotion and cognition than for more observable domains relating to physical health and functioning [29].…”
Section: Discussionmentioning
confidence: 99%